Determinan Keluhan Kesehatan Wanita Usia Subur di Provinsi NTB Tahun 2021 - Nurazizah, Ananda Trinita; Sukim, Sukim (Seminar Nasional Official Statistics, 2023)
Based on BPS data, the percentage of health complaints for Women of Reproductive Age (WUS) in West Nusa Tenggara (NTB) Province in five years (2017-2021) has continued to increase and has become the highest in Indonesia. The importance of WUS health is related to family, community and in giving birth to a healthy generation. In this study WUS health complaints were divided into three categories, that is not health complaints, health complaints not interfering with activities and health complaints interfering with activities. Therefore, this study was conducted using multinomial logistic regression. The results showed that with a significance level of five percent it was proven that the classification place of residence, last education, most activity status, status of living alone, and food insecurity had a significant effect, both on health complaints that did not interfere with activities or interfere with activities. The government is expected to continue to promote the importance of education (at least 12 years), improve mental health counseling programs, and continue to increase efforts to overcome food insecurity.